1993
DOI: 10.3109/00016349309021144
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after surgical correction of tricuspid atresia

Abstract: Tricuspid atresia comprises 1-3% of congenital heart diseases and it is still uncommon in adult patients. We present a case of tricuspid atresia in a young woman who experienced a successful uncomplicated pregnancy after surgical correction of her disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In accordance with these conclusion drawn by Sibai et al, 25 no severe maternal or neonatal events developed in the present (second) reported case of gestational hypertension during pregnancy in a patient with Fontan palliation. 11 Obstetric complications also appear to be a major problem of pregnancy in the context of Fontan palliation (table 3). Intriguingly, including the first pregnancy of patient V, premature rupture of membranes complicated six of the 39 described completed Fontan pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these conclusion drawn by Sibai et al, 25 no severe maternal or neonatal events developed in the present (second) reported case of gestational hypertension during pregnancy in a patient with Fontan palliation. 11 Obstetric complications also appear to be a major problem of pregnancy in the context of Fontan palliation (table 3). Intriguingly, including the first pregnancy of patient V, premature rupture of membranes complicated six of the 39 described completed Fontan pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the right atrium soon deteriorated into a dilated, noncontractile chamber. Pulmonary blood flow was sluggish because blood lost 2 Epidural analgesia NS Carmona et al (1993) 3 Epidural analgesia NS Gerardin et al (1993) 4 Epidural analgesia NS Carp et al (1994) 5 Epidural anesthesia 2% lidocaine (200 mg) with 20 µg sufentanil over 30 minutes Epidural analgesia 0.25% bupivacaine with 250 µg alfentanil bolus CEI 0.1% bupivacaine with 25 µg/cc alfentanil Cohen et al (1994) 6 Spinal analgesia 29G spinal catheter 0.5% hyperbaric marcaine 0.5 cc q 5 min total of 2 cc Braun et al (1996) 7 General 12 General anesthesia NS (emergency C/S) NS Eid et al (2005) 13 General anesthesia RSI; 150 mg propofol, succinylcholine 100 mg, and isoflurane/NO 2 mixture PPV Epidural anesthesia 2% lidocaine with 100 µg fentanyl over 30 min Ioscovich et al (2006) 14 Epidural analgesia/anesthesia 0.1% Bupivacaine with 25 mg meperidine for labor 2% lidocaine plain incremental q 3 min for cesarean section 0.1% Bupivacaine with 1 mg/cc meperidine at 6 cc/hour for postop analgesia Trojnarska et al (2007) 15 NS NS Koraki et al (2009) 16 Epidural anesthesia Ropivacaine 0.75% with 50 µg fentanyl incremental dosing over 30 min Suchonska et al (2008) 17 Epidural anesthesia 0.5% bupivacaine with sufentanil and epinephrine Grim et al (2011) 18 General anesthesia RSI; 0.3 etomidate, succinylcholine 1.5 mg/kg, sevoflurane/O 2 mixture PPV Inoue et al (2013) 19 General anesthesia NS None Caruana et al (2012) 20 Epidural analgesia NS Epidural analgesia NS Abbreviations: NS, not specified; NO2, nitrous oxide; PPV, postive pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%